The Stability of Exchange Networks - Gönül Dogan; M.A.L.M. van Assen; Arnout van de Rijt; Vincent Buskens (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper develops a formal model of exchange network stability that combines expected value theory (Friedkin 1995) with the economic literature on network dynamics. We identify stable networks up to size 8 for varying costs and investigate whether they are Pareto efficient and egalitarian. Only a very small number of networks are stable. Odd cycles and networks consisting of dyads and at most one isolate are the only egalitarian, efficient, and stable networks for a large cost range. We show that some of these results are generalizable to networks of any size and are independent of using expected value theory.
Keywords: D85; 330; Exchange Networks; Stability; Efficiency; Equity; Social Dilemma; Tausch; Netzwerk; Wirtschaftliche Effizienz; Pareto-Optimum; Gleichgewichtsstabilität; Theorie